Biology on track: single-molecule visualisation of protein dynamics on linear DNA substrates. Issue 1 (16th April 2021) - Kaur, Gurleen; Spenkelink, Lisanne M.
Abstract: Single-molecule fluorescence imaging techniques have become important tools in biological research to gain mechanistic insights into cellular processes. These tools provide unique access to the dynamic and stochastic behaviour of biomolecules. Single-molecule tools are ideally suited to study protein–DNA interactions in reactions reconstituted from purified proteins. The use of linear DNA substrates allows for the study of protein–DNA interactions with observation of the movement and behaviour of DNA-translocating proteins over long distances. Single-molecule studies using long linear DNA substrates have revealed unanticipated insights on the dynamics of multi-protein systems. In this review, we provide an overview of recent methodological advances, including the construction of linear DNA substrates. We highlight the versatility of these substrates by describing their application in different single-molecule fluorescence techniques, with a focus on in vitro reconstituted systems. We discuss insights from key experiments on DNA curtains, DNA-based molecular motor proteins, and multi-protein systems acting on DNA that relied on the use of long linear substrates and single-molecule visualisation. The quality and customisability of linear DNA substrates now allows the insertion of modifications, such as nucleosomes, to create conditions mimicking physiologically relevant crowding and complexity. Furthermore, the current technologies will allow future studies on the real-time visualisation of the interfaces between DNA maintenance processes such as replication and transcription.